Genome-wide association analysis reveals the optimal genomic regions for pod size in bean - Li, Mao; Wu, Xinyi; Wang, Baogen; Wu, Xiaohua; Wang, Ying; Wang, Jian; Dong, Junyang; Wu, Jian; Lu, Zhongfu; Sun, Yuyan; Dong, Wenqi; Yang, Jing; et al. (Frontiers in Plant Science, 2023)
The snap bean is the most commonly grown vegetable legume worldwide, and its pod size is both an important yield and appearance quality trait. However, the improvement of pod size in snap beans grown in China has been largely hindered by a lack of information on the specific genes that determine pod size. In this study, we identified 88 snap bean accessions and evaluated their pod size traits. Through a genome-wide association study (GWAS), 57 single nucleotide polymorphisms (SNPs) significantly associated with pod size were detected. Candidate gene analysis showed that cytochrome P450 family genes, WRKY, and MYB transcription factors were the predominant candidate genes for pod development, and eight of these 26 candidate genes showed relatively higher expression patterns in flowers and young pods. A significant pod length (PL) SNP and a single pod weight (SPW) SNP were successfully converted into kompetitive allele-specific polymerase chain reaction (KASP) markers and validated in the panel. These results enhance our understanding of the genetic basis of pod size, and also provide genetic resources for the molecular breeding of pod size in snap beans.